2022
DOI: 10.1370/afm.2781
|View full text |Cite
|
Sign up to set email alerts
|

Communication Gaps Persist Between Primary Care and Specialist Physicians

Abstract: A survey conducted with data from 2008 found that physicians often do not communicate with each other at the time of referral or after consultation. Communication between physicians might have improved since then, with the dissemination of electronic health records (EHRs), but this is not known. We used 2019 survey data to measure primary care physicians' perceptions of communication at the time of referral and after consultation. We found that large gaps in communication persist. The similarity between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Furthermore, empowering GPs to do more was a theme supported by specialists in a recent study in the US. Real world data suggest that a substantial proportion of primary and secondary care physicians do not communicate with each other regarding the patients they jointly care for (Timmins et al 2022). This was in line with comments from the participants in our focus group.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, empowering GPs to do more was a theme supported by specialists in a recent study in the US. Real world data suggest that a substantial proportion of primary and secondary care physicians do not communicate with each other regarding the patients they jointly care for (Timmins et al 2022). This was in line with comments from the participants in our focus group.…”
Section: Discussionsupporting
confidence: 77%
“…Even after widespread dissemination of electronic health records, 34% of primary care physicians in a national study reported that they do not always or most of time receive useful information from specialists about the patients they referred. 2 Despite how common it is for patients to see multiple physicians, care fragmentation has received surprisingly little scientific attention. In this Viewpoint, we propose conceptualizing fragmentation as a pattern of health care utilization that could cause harm and that is related to but distinct from care continuity and care coordination.…”
mentioning
confidence: 99%
“…Having multiple physicians may be appropriate, but it may also lead to medical errors, unnecessary visits, avoidable hospitalizations, and suboptimal care if all of the physicians do not have complete information about the patient and each other’s care plans. Even after widespread dissemination of electronic health records, 34% of primary care physicians in a national study reported that they do not always or most of time receive useful information from specialists about the patients they referred …”
mentioning
confidence: 99%
“…1,2 We highlight 4 papers in this issue that allow us to understand the current state of EHR use, identify unmet needs, provide evidence on their potential to uplift clinical practice and research, and their future potential to improve patient outcomes and address the perpetual problem of the "forgetful health system". [3][4][5][6] Although numerous studies have focused on assessing clinician experience with their EHR systems, few have in parallel obtained the patient's perspective. Meltzer et al, 3 in a survey of health practitioners and their patients from 2 primary care sites, finds discrepancies in experience and attitudes regarding EHR use between patient and clinician.…”
mentioning
confidence: 99%
“…In a survey of over 4,500 clinicians, Timmins et al 4 find that in a substantial number of practices primary and secondary care continue to operate in silos. The study finds in a more motivated group of primary care clinicians, over 20% of clinicians seldom/never send clinical information to specialists and 35% seldom/never receive useful information from specialists.…”
mentioning
confidence: 99%